How do monetary incentives influence prosocial fundraising? An empirical investigation of matching subsidies on crowdfunding - GAO, Zhiyuan (Institutional Knowledge at Singapore Management University, 2020)
Monetary incentives, such as matching subsidies, are widely used in traditional fundraising and crowdfunding platforms to boost funding activities and improve funding outcomes. However, its effectiveness on prosocial fundraising is still unclear from both theoretical (Bénabou and Tirole, 2006; Frey, 1997; Meier, 2007a) and empirical studies (Ariely et al., 2009; Karlan and List, 2007; Rondeau and List, 2008). This dissertation aims to examine the effectiveness of matching subsidies on prosocial fundraising in the crowdfunding context. Specifically, I study how the presence of matching subsidies affects overall funding outcomes and funding dynamics in the online prosocial crowdfunding environment. The first essay utilizes a quasi-experiment on a prosocial crowdfunding platform to examine the effectiveness of matching subsidies, in which third-party institutions provide a dollar-for-dollar match of private contributions on selected campaigns, on funding outcomes, and lender behavior. Although matching subsidies offer matched loans competitive advantages over unmatched loans, we find that the total private contributions to both matched and unmatched loans increase compared to their pre-matching counterparts, suggesting a positive spillover effect on unmatched loans. However, matching subsidies lead to decreased private contributions on the platform after the matching event, showing an intertemporal displacement effect on existing loans. Furthermore, we find matching subsidies effectively attract previously inactive lenders to contribute to matched loans, leading to a motivational crowding-out effect on active lenders to unmatched loans. These findings shed new light on the overall effectiveness of matching subsidies on the online crowdfunding platforms. These findings provide policy support to offer matching subsidies on prosocial crowdfunding websites to increase overall funding. The second essay examines how matching subsidies affect the dynamics of prosocial crowdfunding, driven by herding behavior and payoff externalities. First, in contrast to the previous literature documenting that prior contributions may crowd out subsequent contributions in prosocial crowdfunding, we find that both herding behavior and positive payoff externalities exist, which suggests that higher cumulative contributions lead to an increase in the subsequent funding amount. Second, we identify the existence of the bystander effect, where the positive effect of prior contributions drops sharply when the campaign is close to success. Finally, we find a substitution effect between matching subsidies and prior cumulative contributions. Matching subsidies not only increase private contributions but also moderate the herding behavior and payoff externalities. Our findings shed new light on the effective strategies to boost fundraising on prosocial crowdfunding platforms.